SOCIAL BEHAVIOR OF BRAZILIAN ORGANIZATIONS: AN ANALYSIS OF ISOMORPHISM MECHANISM - Bogo, Adelaide Maria; Schmitt, Alan Christian; Henning, Elisa; Menegotto, Margarete L.A. (Brazilian Journal of Operations & Production Management, 2017)
Human's behavior is determined by variables that are commonly understood as needs and motives and, in general, it is motivated by a desire to achieve some goal. According to Maslow, these needs are construct on a hierarchy composed of five groups - physiological, safety, love/belonging, esteem and self-actualization. In order to fulfill these needs, organizations have social behavior to address the issues of human beings, individually or collectively way. Therefore, identifying the types of actions performed and then analyzing them in the context of basic human needs, will allow us to understand isomorphic features in the social behavior of these organizations. In this sense, this study aims to analyze the social behavior of Brazilian organizations and the existence of isomorphism in these practices. The sample consists of companies listed on the ISE-BOVESPA stock market and the data were collect in the Sustainability Reports. The methodology utilize Content Analysis technique to define the categories and descriptive statistics to understand the isomorphic behavior. The findings indicate a concentration of actions on the need for ‘Safety’ and the existence of coercive and normative isomorphism in social activities for internal audiences and mimetic isomorphism in actions aimed at external audiences.